Особенности систем тестирования для средней школы - Коряк, А. С. (УАДО, 2004)
In this article we describe the problem of development testing system for secondary school. Testing system is an important part of distance learning and taking into account the specific of school education, testing system has to answer the purpose of such education system and be flexible, comfortable and clear for users. During the creating our testing system we were confronted with difficulties. The rules for development and maintenance of testing system which are proposed in this article help us to tackle these difficulties.
Keywords: тестирование для средней школы